Efficacy of 5 µg and 10 µg Dexmedetomidine as Adjuvants to 3 mL 0.5% Hyperbaric Bupivacaine in Pelvic and Lower Limb Orthopaedic Surgeries: A Randomised Clinical Study - Jigisha Bharatbhai Mehta; Shreya Jatin Patel; Nilesh Vrajmohan Shah; Dinesh K Chauhan; Sara Mary Thomas (Journal of Clinical and Diagnostic Research)
Introduction: Low-dose bupivacaine used in spinal anaesthesia results in speedy recovery. For lower limb orthopaedic surgeries, to provide sufficient anaesthesia and prolong postoperative analgesia in a less cumbersome way, author can add potent adjuvants like dexmedetomidine (an alpha-2 adrenergic receptor agonist) in effective and safer doses intrathecally. Aim: To compare the effects of intrathecal 5 μg dexmedetomidine versus 10 μg dexmedetomidine as adjuvants to 3 mL of 0.5% hyperbaric bupivacaine in pelvic and lower limb orthopaedic surgeries. Materials and Methods: This randomised clinical and single-blind study study was conducted at the Operation Theatre (OT) complex of Dheeraj Hospital, SBKS, and MIRC, Sumandeep Vidyapeeth, Vadodara, Gujarat, India in the Department of Anaesthesia over a period of 18 months, from September 2022 to March 2024 and total of 82 patients scheduled for lower limb and pelvic orthopaedic surgery who were to receive spinal anaesthesia were divided into Group D1 and D2. Group D1 (n=41) received 3 mL of bupivacaine (0.5% heavy) with 5 μg dexmedetomidine, totaling 3.1 mL, while group D2 (n=41) received 3 mL of bupivacaine (0.5% heavy) with 10 μg dexmedetomidine, also totaling 3.1 mL intrathecally. The onset and duration of sensory and motor blockade, as well as the duration of analgesia, were noted, along with the monitoring of haemodynamic parameters and any side effects. All observed data were analysed using statistical tests such as the unpaired t-test and Chi-square test. A p-value <0.05 was considered statistically significant. Results: Demographic data were comparable in both groups and were non significant (p-value >0.05). The onset of sensory block was earlier in group D2 (2.01±0.12 min) than in group D1 (2.87±0.36 min) (p-value <0.05). The onset of motor block was also earlier in group D2 (2.63±0.26 min) compared to group D1 (3.36±0.43 min). The duration of sensory block was longer in group D2 (457.46±32.85 min) than in group D1 (318.02±32.27 min). The duration of motor block was also longer in group D2 (396.17±36.13 min) than in group D1 (257.37±25.02 min) (p-value <0.05). The duration of analgesia and the time until the need for the first rescue analgesia was significantly longer in group D2 (364.29±43.64 min) compared to group D1 (219.51±23.39 min). Conclusion: Intrathecal bupivacaine with dexmedetomidine at a dose of 10 μg results in an earlier onset and longer duration of sensory and motor block compared to a dose of 5 μg. The duration of postoperative analgesia was longer, and the time until the need for the first rescue analgesia was extended with the 10 μg dosage. No significant side effects were observed in either group.